PERSPEKTIF PENINGKATAN PRODUKSI PADI DI KABUPATEN LAMONGAN - Alviyah Yunianti; Elys Fauziyah (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2015)
The aim of this research are to know the result of rice product forecasting at Lamongan  regency  in  2016  and  identify  the  factor  influence  rice  production. This research  was  done  at  Lamongan  by  using  cluster  method.  The  total  number  of respondents are 60 farmers. Data were analyzed with ARIMA and multiple regression method. The results show that the rice  production forecasting at Lamongan in 2016 will  increas  approximately  1.022.488  ton,  and  the  factors  influence  rice  production are land area, urea, labor and capital. If each those variables are increased, it will be able to increase the result of rice production.